The Role of Digital Dental Radiography in Private Dental Clinic in Kirkuk, Iraq: Opportunities and Barriers in Disaster Victims Identification - Jasim, Raied Mohammed; Galib, Zaynab Abdulameer (Acta Odontologica Indonesia, 2025)
Evaluating the count of X-rays in private dental clinics using extraoral digital X-ray in Kirkuk, Iraq, and its role in mass disasters—natural or man-made—assesses opportunities and barriers for use as antemortem data, especially in situations where other identification methods are impossible, excluded, or costly. The success of the identification process depends on the availability of well-preserved antemortem data and accessibility to that data. Three private dental centers in Kirkuk (Alpha1, Alpha2, Panoramic) were selected according to criteria such as use of the same digital X-ray equipment, availability of archived dental records, and consent for participation and site access.Data was collected from 2022 to 2024: only Alpha1 center was operational from August 1, 2022. Scan counts were 391, 305, and 345 annually, with steady population growth (1.05M → 1.10M). By 2025, in addition to Alpha1, Alpha2 and Panoramic centres were operating. Data collected until May 1, 2025, showed scan records reaching 1,668 — a 383% increase from 2024. There was a positive percentage change. The cumulative total number of scans reached 2,709. The cumulative percentage was 0.245 compared to the city center population of 1,128,000. Limitations of this study include a small sample size, lack of assessment of actual performance in a real disaster victim identification event, and the early start date of Alpha2 and Panoramic centres, so their data reflect only the initial implementation phase.The total number of X-rays represents a reference that can be used as antemortem data for disaster victim identification, especially in Kirkuk, Iraq. Availability of medical imaging infrastructure can directly and rapidly increase the amount of stored data and service provision, which is a vital resource during mass casualty events requiring disaster victim identification.